Respiratory Syncytial Virus-Associated Hospitalizations in Children With Neurological Disorders, 2006–2015. (10th July 2021) - Rose, Erica Billig; Dahl, Rebecca M; Havers, Fiona P; Peacock, Georgina; Langley, Gayle E
Abstract: Background: We quantified the risk of respiratory syncytial virus (RSV) hospitalizations and severe outcomes among children with neurological disorders. Methods: We estimated RSV-specific and RSV-associated hospitalization rates using International Classification of Diseases, Ninth Revision (ICD-9) codes from 2 insurance claims IBM MarketScan Research Databases (Commercial and Multi-State Medicaid) from July 2006 through June 2015. For comparison, a simple random sample of 10% of all eligible children was selected to represent the general population. Relative rates (RRs) of RSV hospitalization were calculated by dividing rates for children with neurological disorders by rates for children in the general population by age group and season. Results: The RSV-specific hospitalization rate for children with any neurological condition was 4.2 (95% confidence interval [CI]: 4.1, 4.4) per 1000 person-years, and the RSV-associated hospitalization rate was 7.0 (95% CI: 6.9, 7.2) per 1000 person-years among children <19 years of age. Among privately insured children, the overall RR of RSV hospitalization in children with neurological disorders compared with the general population was 10.7 (95% CI: 10.0, 11.4) for RSV-specific hospitalization and 11.1 (95% CI: 10.5, 11.7) for RSV-associated hospitalizations. Among children in Medicaid, the RSV-specific hospitalization RR was 6.1 (95% CI: 5.8, 6.5) and the RSV-associated hospitalization RR was 6.4 (95% CI: 6.2, 6.7) compared with the general population. Conclusions: Our population-based study of children with neurological disorders found that the risk of RSV hospitalization was 6 to 12 times higher among children with neurological disorders than among the general pediatric population. These findings should be considered when determining who should be targeted for current and future RSV interventions. Abstract : This population-based study of children with neurological disorders found that their RSV hospitalization rates were 6 to 12 times higher than children in the general population. These findings are important for targeting current and future RSV interventions.